Biskop Th. Skat Rørdam og Kirkefondet - Trock, Carl (Kirkehistoriske Samlinger, 1997)
»Københavns Kirkefond« (the Church Fund of Copenhagen) and its antecedents have been described several times - recently by Kamma Struwe. This article is about its beginnings prepared by some years of cooperation between the grundtvigian Th. Skat Rørdam, who in 1895 became bishop of Zealand including Copenhagen, and a group of gifted laymen who were passionately engaged in remedying the ailing church in the capital. In 1890 they had set to work on changing the conditions in the new parts of the rapidly growing city where the building of churches had almost stopped, and they had started collecting money to this end. The bishop and the laymen more or less agreed about the goal: to forward an active congregational life. They also agreed about the means to obtain this goal: more churches and more ministers. The ministers were to have a field of activity of manageable size so that people knew who their minister was and so that the minister was able to reach the members of his congregation. The collaboration had started in a state church commission set up in 1890 to improve the conditions of the church in Copenhagen. During the following years it continued and with the creation of »Kirkefondet« in 1897 it got a permanent form. By the turn of the century it had collected money for 13 churches or church rooms and for the complete or partly payment of 21 ministers. In spite of the distrustfulness of Conservative ministers of the capital this voluntary work was integrated in the existing parish structure of the National Church because of the increasing understanding of the Ministers of Ecclesiastical Affairs for the work of the Church Fund. This private work was indeed necessary because in the early eighteen nineties the Danish politicians only half-heartedly went in for the idea that the state supported the building of churches. It was said that the capital was rich and could manage on its own. But actually the Parliament defied the words of the constitution that the state must support the National Church. For some time the municipality of Copenhagen was rather benevolent and donated building sites for churches as well as cash contributions. But the resistance against these measures increased, and the constitution also stated that nobody is bound personally to contribute to any other worship of God than his own. In 1895 the Left Reform Party (Venstrereformpartiet) with J.C. Christensen as its leader gained the majority in the Danish Parliament and the opposition against the increasingly weaker Conservative governments continued to grow. The school teacher J.C. Christensen managed to change the resistance of his party against the state support of the building of churches: The constitution had to be respected. His party was able to tolerate that the municipality gave building sites for churches, but it strongly rejected the granting of money from the municipal budget for church building. In this respect the constitution was followed too. A real church tax the party found undesirable - also for the sake of the church itself since the resistance against it was so strong. In 1900 J.C. Christensen introduced a bill about vestries in the parishes elected on a broad basis. This summoned a new era but bishop Rørdam and the governors of the Church Fund as a matter of course were against giving the majority of people so much influence. The bill also caused damage to the active congregational life in Copenhagen and what it had achieved.